Family grief during the COVID-19 pandemic: a meta-synthesis of qualitative studies - Pamela Perina Braz Sola; Carolina de Souza; Elaine Campos Guijarro Rodrigues; Manoel Antônio dos Santos; Érika Arantes de Oliveira-Cardoso (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
The COVID-19 pandemic has led to a public health crisis, with increases in the number of deaths. As a result, the number of bereaved people has increased significantly. In addition, the measures adopted to control the spread of virus have triggered changes in the subjective and collective bereavement experiences. This systematic literature review aims to summarize and reinterpret the results of qualitative studies on the experience of losing family members during the pandemic by a thematic synthesis. The searches were performed in the Web of Science, Scopus, PubMed/MEDLINE, CINAHL, PsycINFO, and LILACS databases. Among 602 articles identified, 14 were included. Evidence was assessed using the Critical Appraisal Skills Programme tool. Two descriptive themes related to the objective were elaborated in addition to one analytical theme, namely: "Pandemic grief: lonely and unresolved". These themes proved to be interrelated and indicate that experiences of loss in this context were negatively impacted by the imperatives of physical distance, restriction of hospital visits, technology-mediated communication, and prohibition or restriction of funerals. These changes resulted in experiences marked by feelings of loneliness and helplessness, which should be considered when planning intervention strategies that favor communication between family members with the afflicted loved one and with the health care team, enabling welcoming and creating alternatives for farewell rituals. The findings may support further research to test intervention protocols, especially to guide public policies and promote psychological support to bereaved family members after their loss.